Efektivitas Penggunaan Alat Peraga Kodama dalam Mengerjakan Soal Matematika - Herlina Ahmad (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2017)
This study aims to determine the effectiveness of the use of Kodama props in the process of doing Mathematics exercises material The equation of straight line conducted in SMPN 5 Wonomulyo VIII classroom learners by looking at the learning outcomes, activities and responses of learners. This type of research is a quasi experimental research involving 2 different groups but has a homogeneous ability. The population in this study were all students of class VIII SMPN 5 Wonomulyo which amounted to 177 people. The sample of this research is the students of class VIII C as the experimental class and class VIII D as the control class. Data collection is done through tests, observation sheets and response questionnaires. The data of the research were analyzed by descriptive analysis and inferential analysis. The result of the research based on descriptive analysis in the experimental class obtained an average value of 79,86 > KKM or 80% classical completeness, reaching 82,76%. Based on the inferential analysis, the ost test value is obtained with the degree of freedom 58 hence obtained at 1,67. Because it is larger than it is rejected and accepted, it means at a 95% confidence level statement that the average value of the experimental class is higher than the average value of the control class is acceptable. It can be seen that the value of post test experimental class completeness is 82,759 % or 24 students from 29 students over KKM. Based on the analysis of the instrument nontes obtained activity learners experimental group meets the criteria of effectiveness of reaching 57,59% and the response of learners are in the positive category with an average value of 78,28%. It can be concluded that Kodama props can improve learning outcomes of students of class VIII SMPN 5 Wonomulyo and able to make learners spirit in doing Mathematics.